Structured Arrangement Supporting The Development of Splitting Level in Doing Multiplication By Number Up To 20 - Meryansumayeka, Meryansumayeka; Darmawijoyo, Darmawijoyo; Hertog, Jaap den; Ilma, Ratu (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
In guiding students to construct a mathematical concept themselves, learning process should be started by a context which is suit with the concept. In this research, we focused on structured arrangement which was believed to be able to support students ages 8 Ã¢â‚¬â€œ 9 years old developing splitting strategy in doing multiplication. This study was a design research underlined by tenets of Realistic Mathematics Education (RME). The result show that giving structured objects, recognizing number relation in multiplication, and maintaining flexible calculation have important roles in supporting the development of mental calculation achieving splitting level.Key words: design research, mental calculation, splitting level, structured arrangementÃ‚Â DOI: http://dx.doi.org/10.22342/jme.2.2.748.199-214